Ultrafast magnon generation in an Fe film on Cu(100) - A. B. Schmidt and M. Pickel and M. Donath and Pawel Buczek and Arthur Ernst and V. P. Zhukov and P. M. Echenique and Leonid M. Sandratskii and E. V. Chulkov and M. Weinelt (Physical Review Letters, 2010)
We report on a combined experimental and theoretical study of the spin-dependent relaxation processes in the electron system of an iron film on Cu(100). Spin-, time-, energy- and angle-resolved two-photon photoemission shows a strong characteristic dependence of the lifetime of photoexcited electrons on their spin and energy. Ab initio calculations as well as a many-body treatment corroborate that the observed properties are determined by relaxation processes involving magnon emission. Thereby we demonstrate that magnon emission by hot electrons occurs on the femtosecond time scale and thus provides a significant source of ultrafast spin-flip processes. Furthermore, engineering of the magnon spectrum paves the way for tuning the dynamic properties of magnetic materials. © 2010 The American Physical Society.